Dynamic performance of reinforced concrete beams and joints subjected to impact loads - Li, Huawei (Curtin University, 2021)
This thesis performs analytical, numerical and experimental studies to investigate the influences of various parameters that affect the drop-weight impact tests, and the impact responses of monolithic and precast reinforced concrete beams, and beam-to-column joints. Influences of the drop weight test setup configurations and measurement methods on impact force and impact response of beams are examined. Performances of precast concrete beams and beam-to-column joints subjected to impact loads and their impact resistance capacities are investigated.